Hematology of layers chickens vaccinated with fowl cholera vaccine and experimentally inoculated with virulent Pasteurella multocida serotypes in Zaria, Nigeria - Lekko, Yusuf Madaki; Wakawa, Aliyu Mohammed; Abdu, Paul Ayuba; Raji, Moshood Abiola; Mamman, Paul Habila; Audu, Yusuf; Balami, Saraya Yaro; Ezema, Kingsly Uwakwe; Omeh, Isaac John; Mishelia, Peter Anjili (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The objective of this study was to evaluate some hematological parameters in commercial layers inoculated with two virulent Pasteurella multocida serotypes. Materials and Methods: A total of 84 twenty-week-old black Harco layers were randomly assigned to seven groups (A, B, C, D, E, F and G) with 12 birds per group. 1mLof live attenuated fowl cholera (FC) vaccine was administered subcutaneously at 24 weeks of age to groups A and B, emulsified inactivated (killed) FC vaccine was administered dosed at 0.5 mL per bird subcutaneously at 24 weeks of age to groups C and D, groups E and F were not vaccinated, while group G served as control. Groups A, C and E were inoculated with P. multocida serotype A:1 and groups B, D and F were inoculated with P. multocida serotype A:3. Using McFarland Standard, each bird received a dose of 0.5 mL (0.1 mL intranasally and 0.4 mL intramuscularly) containing 4.5 x 108 cfu/bird. Results: For PCV (P?0.2692 and P?0.7643) and HB (P?0.2806 and P?0.7266) on day 2 and 10 post inoculation, there was no significant difference between the vaccinated, non-vaccinated groups and control group G. However, there was a highly significant difference P?0.05 in the mean concentrations of ALP between the control group G (67.67±1.453 u/l) vaccinated groups A (80.33±4.98 u/l), B (81.33±2.60 u/l), C (75±6.35 u/l), and D (84±5.132 u/l) and unvaccinated groups E (104±1.528 u/l ), and F (78 ±3.512 u/l) post inoculation. Conclusion The PCV significantly decrease P?0.05 in layers vaccinated and inoculated with P. multocida but increase in unvaccinated layers inoculated P. multocida. The mean serum ALP concentration significantly increase P?0.05 in unvaccinated layers inoculated with P. multocida when compared to layers vaccinated and inoculated with P. multocida. http://doi.org/10.5455/javar.2017.d216